Effect of external lumbar supports on joint position sense, postural control, and postural adjustment: a systematic review - Azadinia, Fatemeh; Kingma, Idsart; Mazaheri, Masood (Disability and rehabilitation, 2023)
To review the effects of external lumbar supports on various aspects of sensorimotor function including joint position sense (JPS), postural control, anticipatory postural adjustments (APAs), and compensatory postural adjustments (CPAs). A systematic literature search was performed in PubMed, EMBASE, Scopus, Ovid, Cochrane library, and Web of Science. Two reviewers selected studies which assessed the effect of lumbosacral orthosis or kinesio-tape on JPS, postural control or APAs/CPAs in subjects with and without low back pain (LBP). The methodological quality of included studies was assessed using a modified version of Downs and Black's checklist. Findings demonstrated moderate effects of lumbosacral orthosis on specific aspects of sensorimotor control including JPS and to a lesser extent standing stability. These domains were not or minimally affected by application of kinesio-tape. Both orthosis and kinesio-tape had negligible effects on APAs and CPAs. The positive effects of lumbar orthosis on JPS or postural control were mostly observed in conditions where sources of proprioceptive feedback are impaired (such as LBP) or absent (standing with eyes closed on an unstable surface). However, evidence does not prove significant positive effects for the application of kinesio-tape to improve sensorimotor control. IMPLICATIONS FOR REHABILITATION Wearing lumbar orthosis leads to an improvement in joint position sense. Postural stability seems to be affected to some extent by utilizing lumbar orthosis. Clinicians can administer orthosis to improve sensorimotor adaptation, especially in conditions with poor proprioception. Kinesio-tape had negligible effects on all domains of sensorimotor control. Improvement of sensorimotor function as a result of application of kinesio-tape is questionable.